(untitled) (Patan Prospective Journal, 2023)
The main objective of this research is to study of impact of meteorological parameters on atmospheric turbidity index on Lumbini (27.49o N, 83.28o E, 110 m asl), Nepal for a period of one year (2018). The ground based data of spectral aerosol optical depth (AOD) are derived from Aerosol Robotic Network (AERONET) of NASA. Satellite based data of meteorological parameter (maximum temperature, minimum temperature, dew point, relative humidity, water contend and rainfall) are downloaded from NASA website. Daily, monthly and seasonal variation of atmospheric turbidity is analyzed. The annual average of Angstrom exponential ( α), Angstrom coefficient of turbidity ( β) and Linke turbidity factor (LT) are found 1.0 ± 0.2, 0.36 ± 0.20 and 8.3 ± 2.5 respectively. Correlation coefficient of meteorological parameters with atmospheric turbidity is analyzed. No significant effect of maximum temperature, minimum temperature, dew point and water contend on atmospheric turbidity. There is positive effect of rainfall on α, but negative effects of relative humidity and rainfall on β and LT. Atmospheric turbidity index is an important for the air pollution. Result of this research work is beneficial for the further identification, impact and analysis of atmospheric turbidity index on meteorological parameters at different places with same geographical condition.